Keterlibatan Orang Tua dalam Mengenalkan Sains untuk Anak Down Syndrome - Yubaedi Siron; Tiara Pridasari Setianingtias; Ayu Iis Nuryanah; Dina Nur Fauziah; Eva Indriyani; Sahriatul Romdah; Savitri Zahirah (JECED : Journal of Early Childhood Education and Development, 2022)
This study describes parents' involvement in introducing science to children with down syndrome. This study used a qualitative approach. The research participants were 6 parents with Down syndrome children at 4-8 years old. The purposive sampling method was used to involve the participants. Data were collected through semi-structured online interviews. Analysis of the data in this study using Miles and Huberman. The results of this study show how parents introduce science activities by introducing science activities using simple methods, the media used by utilizing household appliances and objects in the surrounding environment. Parents consider science activities essential to be introduced to children. However, parents face challenges because children are difficult to manage, do not easily focus, and are easily bored.